A Foretaste of Heaven : Musical Teleology in Mozart's Ave verum corpus, K618 - Suurpää, Lauri (Cambridge University Press, 2024)
In June 1791, having composed almost no church music for ten years, Mozart wrote the short motet Ave verum corpus, k618, a setting of the Latin medieval eucharist hymn. The theological teleology in the text introduces a process-like aiming at a goal that cannot, however, be reached. This study is about how teleology operates in the motet – the ways in which the text's ultimately unfulfilled goal-directed processes operate in Mozart's music. The music is approached from a variety of analytical perspectives that reflect different aspects of this theme: the new Formenlehre and phrase structure, topic theory, and the analysis of voice-leading structure, register and hypermetre. Together, these approaches elucidate the multiplicity of musical processes that, as in the motet's text, announce a goal but fail to reach it. This article has been published in a revised form in Eighteenth-Century Music, https://doi.org/10.1017/S1478570623000258. This version is free to view and download for private research and study only. Not for re-distribution or re-use. © The Author, 2024.
Keywords: musiikki; musiikkianalyysi; motetit; kristinusko; teologia; kirkkomusiikki; musiikkifilosofia; teleologia; musiikinteoria